Natural and anthropogenic factors of flooding in the Saptakoshi alluvial fan, east Nepal - Thakur, Pramod Kumar; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2004)
The Saptakoshi alluvial fan (SAF), located in front of the Sub Himalaya near the Chatara village, is one of the largest fans in the world. Floods bring about severe loss of lives and property in the middle and lower reaches of the Saptakoshi River. This paper attempts to assess the natural as well as anthropogenic factors responsible for flooding in the SAF. Some of the major factors of flooding are continuous and high-intensity monsoon rainfall, huge discharge of the Saptakoshi River, unconsolidated sediments and soft rock constituting steep slopes, deforestation, and land degradation. A risk zonation map of the SAF was prepared by analysing these factors, and the SAF was classified into low, medium, and high risk zones. The villages situated in the south-western part of the SAF (i.e., Belardaha, Bhardaha, Joginia, Hanumannagar, Birpur, and Tilathi) lie in a high risk zone, whereas those lying in the eastern portion (i.e., Chatara, Mahendranagar, Singra, lnaruwa, and Diwanganj) belong to a low risk zone. The flood risk level on the south-western bank is high mainly because of water impoundment by the barrage and indiscriminate release of floodwater towards the western flank of the Saptakoshi River.